Markers of autoimmune liver diseases in postmenopausal women with osteoporosis - Demirdal, Umit Secil (2010)
INTRODUCTION: Osteoporosis is a common complication of chronic liver diseases. However, there is limited information about autoimmune liver diseases as a factor of secondary osteoporosis. Therefore, we aimed to investigate the autoantibodies of autoimmune liver diseases in patients with osteoporosis. METHODS: One hundred fifty female patients with postmenopausal osteoporosis were included. Bone mineral density was measured by dual energy X-ray absorptiometry. We analysized autoantibodies including antinuclear antibodies, liver membrane antibodies, anti-liver/kidney microsomal autoantibodies1, liver-specific protein, antismooth muscle antibodies, and anti-mitochondrial antibodies by indirect immunofluorescence. Serum was assayed for the levels of aminotransferases. RESULTS: The mean age of the patients was 63,13±8,6 years. The mean values of L1-L4 T-scores and femur total T-scores were -3,08±0,58 and -1,53±0,81, respectively. Among the 150 patients with osteoporosis, 14 (9.3%) were antinuclear antibodies, four (2.7%) were liver membrane antibodies, three (2.0%) were anti-liver/kidney microsomal autoantibodies1, and two (1.3%) were liver-specific protein positive. None of the patients had anti-mitochondrial antibodies or smooth muscle antibodies positivity. The mean values of levels of aminotransferases were within normal range. CONCLUSIONS: The presence of liver membrane antibodies, liver-specific protein, and anti-liver/kidney microsomal autoantibodies1 has permitted us to see that there may be some suspicious clues of autoimmune liver diseases in patients with osteoporosis as a secondary risk factor. On the other hand, there is a need for comprehensive studies with a larger sample size and studies designed to compare the results with a normal population to understand the clinical importance of our findings.